The Changing Basis of Political Conflict in Advanced Western Democracies - Arwine, A. author. aut Link
XIV, 119 p.
Keywords: Political conflict in Western democracies has traditionally emerged from politics rooted in competing ideologies and interests. With the rise of politics of identity, political conflict is morphing as political parties align themselves with identities, rather than ideologies or interests.